Standard R 7.0.100-2018: from difficulties to opportunities - M. Yu. Neshcheret (Библиосфера, 2021)
The article presents an overview of the problems that arise in theprocess of practical application of the national standard regulating the rules of bibliographic description in bibliographic activities. Special attention is paidto the features of the bibliographic description that have not received sufficient coverage in the standard. The article emphasizes that the standard is focused on a creative approach to the application of description rules. It offers various options, the choice of which depends on the specifics of a particular library, the purpose of the description and the information needs of the user. At the same time, the methodological decisions of the compilers of the bibliographic description are subjective. They depend not only on the tasks facing the bibliographic institution, but also on the qualifications of the bibliographers. It is necessary to adjust the adoption of methodological decisions by preparing normative and methodological materials that explain and detail the provisions of the basic standard.